Clinical Study on Skin of Layered Emulsion Containing Scutellaria baicalensis Root Extract - Choy, Yoon-Jung; Kim, Gyu-Ri (Asian Journal of Beauty and Cosmetology, 2024)
Purpose: The skin, particularly the stratum corneum, plays a crucial role in protection and moisture retention. Scutellaria baicalensis, well-known for its anti-inflammatory and antimicrobial properties, was studied for its potential to alleviate itch associated with atopic skin.Methods: A lamellar structured emulsion containing Scutellaria baicalensis root extract was prepared and tested on 21 adults. Participants applied the emulsion twice daily for 4 weeks. Skin surface moisture, tran-sepidermal water loss (TEWL), and itch severity were measured at baseline, after 2 weeks, and after 4 weeks using Corneometer CM825, Tewameter® TM 300, and visual analog scale (VAS), respec-tively. Adverse reactions were monitored. Statistical analysis was performed using SPSS Statistics 26.Results: Itch severity decreased significantly (6.86 to 2.81, p<0.001). No adverse reactions were reported.Conclusions: The emulsion significantly improved skin hydration, reduced TEWL, and alleviated itch, indicating its potential for enhancing skin barrier function and addressing dermatological concerns.